COMPARISON OF PUBLIC'S INTEREST IN SELECTING TRADITIONAL AND MODERN MEDICINE THERAPY - FITRIAH, RAHMAYANTI; HIDAYATI, RAHMI; MUTHIA, REZKY HENY (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aims to determine the public's interest in selecting traditional medicine or modern medicine and the factors that influence this interest in Loktabat Selatan Village, Banjarbaru City, South Kalimantan Province, Indonesia. Methods: The research method used a Cross-Sectional approach. The data were collected from 100 respondents of Loktabat Selatan Village people, Banjarbaru City, using an instrument in questionnaire form. Results: The comparison result of the interest of the therapy choice showed in traditional medicine interest was 58%, and modern medicine was 42%. For the comparison of respondents' interests results based on internal factors were 55.2% which was a decent category, and external factors were 53.4% which was enough category. Data analysis using the Chi-Square test obtained a sig value of 0.814>0.05, then H0 is accepted. Conclusion: There is a comparison of public interest in selecting of traditional and modern medicine therapy in South Loktabat Village, Banjabaru City, South Kalimantan Indonesia.